2005
DOI: 10.1002/art.21474
|View full text |Cite
|
Sign up to set email alerts
|

Association of prevalent and incident knee cartilage defects with loss of tibial and patellar cartilage: A longitudinal study

Abstract: Objective. To describe the association between prevalent and incident knee cartilage defects and loss of knee cartilage in male and female adults.Methods. A convenience sample of 325 subjects (mean age 45 years; age range 26-61 years) was evaluated at baseline and ϳ2 years later. Knee cartilage volume, cartilage defect scores (0-4 scale), and joint surface area were determined using T1-weighted fatsuppression magnetic resonance imaging techniques. Height, weight, and radiographic evidence of osteoarthritis wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
80
0
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 120 publications
(87 citation statements)
references
References 31 publications
5
80
0
1
Order By: Relevance
“…Reviewing the literature, quantification of cartilage morphometry yields a variety of results: some studies have demonstrated that MRI of the knee cartilage is a sensitive way of quantifying cartilage loss in OA [8,9,53,[56][57][58][59][60][61][62][63], whereas other authors could not demonstrate a [46,64]. This might be in part explained by the increase of water content and consequently swelling of the cartilage in the early stages of OA leading to an enlargement of the cartilage volume.…”
Section: Discussionmentioning
confidence: 97%
“…Reviewing the literature, quantification of cartilage morphometry yields a variety of results: some studies have demonstrated that MRI of the knee cartilage is a sensitive way of quantifying cartilage loss in OA [8,9,53,[56][57][58][59][60][61][62][63], whereas other authors could not demonstrate a [46,64]. This might be in part explained by the increase of water content and consequently swelling of the cartilage in the early stages of OA leading to an enlargement of the cartilage volume.…”
Section: Discussionmentioning
confidence: 97%
“…Cartilage defects, which are irregularities on the surface of the usually smooth articular cartilage, are becoming recognized as important early determinants of potential arthritic change, particularly at the knee. 2,3 These defects are graded according to the depth of loss of cartilage thickness. Clinically, knee cartilage defects have been correlated with pain and functional impairment, [4][5][6] and have been shown to predate localized cartilage loss and disease progression, 7 including the risk of total knee replacement.…”
Section: Introductionmentioning
confidence: 99%
“…MRI. MRI of the right knee was performed as described previously (12)(13)(14). Knees were imaged in the sagittal plane on a 1.5T whole-body MR unit (Picker International), using a commercial transmit-receive extremity coil at the baseline visit and at the 2-year and 10-year followup visits.…”
Section: Significance and Innovationsmentioning
confidence: 99%
“…The presence of any cartilage defect was defined as any score $2. Intraobserver reliability (expressed as intraclass correlation coefficient [ICC]) ranged from 0.89-0.90 (13). Interobserver reliability was assessed in 50 MR images and yielded an ICC of 0.85-0.90 (13).…”
Section: Significance and Innovationsmentioning
confidence: 99%